G164(P) A tale of two guidelines: The diabetic ketoacidosis intravenous fluids anomaly. (24th May 2017) - Javed, MS; Muhammad, BJ
Abstract : Introduction: NICE NG18 includes guidelines on diabetic ketoacidosis (DKA) management in children and young people up to their 18th birthday. In most hospitals, a diabetic young person in DKA is managed by adult medical teams using adult guidelines. Most in-patient medical units follow Joint British Diabetes Societies Inpatient Care Group (JBDSICG) recommendations (2013) to calculate intravenous fluid. Aim: We aimed to analyse the difference in fluids given to young people if they are treated for DKA using adult guidelines and compare that with NICE NG18. Methods: Since risk of cerebral oedema is highest within first 12 hours of treatment of DKA, we worked out the volume of intravenous fluids administered to a young person of different weights within first 12 hours of treatment using NICE NG 18 and JBDSICG 2013 recommendations. We used UK-WHO Growth Charts to workout average weight of boys and girls at ages 16 to 18 years. We used Microsoft Excel 2016 to plot the data to highlight difference in fluid calculation between adult and paediatric guidelines. Results: In contrast to the paediatric DKA guidelines, fluid administered as per adult guidelines is not calculated based on weight of the patient. For a young person in DKA with 5% dehydration and weighing 60 kg, if no fluid bolus is given then paediatric guidelines would recommend administration of 1230 ml in contrast to 4750 ml recommended by adult guidelines in first 12 hours of treatment. If one fluid bolus is given, then this young person would have 1830 mls within first 12 hours of treatment as per paediatric guidelines in contrast to 5250 mls as per adult guidelines. The difference amounts to 65%–74% less fluid recommended by paediatric guidelines. The difference is greater if young person weights less than 60 kg. The difference is smallest but still significant for a young person weighing 100 kg. Conclusion: Treating young people in DKA in adult wards using NICE NG18 will need a huge culture change. Until that happens, great care must be exercised in treating these young people with adult guidelines. Studies are needed to identify incidence of DKA associated cerebral oedema in young people.